Understanding the Relationship between Iron and Lipid Metabolism in Non-alcoholic Fatty Liver Disease - Singh, Abhishek Kumar (Curtin University, 2022)
This research shows that in the absence of steatosis short term iron exposure appears to improve mitochondrial function and decrease mitochondrial fatty acid breakdown. In contrast, in the presence of hepatic steatosis, iron increased peroxisomal fatty acid breakdown. Importantly, iron decreased the number of cholesterol crystals present in fatty liver. These results suggest iron loading in steatosis may act to reduce liver damage in non-alcoholic fatty liver disease.